Examining attention cues for learning 3D modelling software: an eye-tracking study on instructional screencast - Sharmila Devi Pachiyappan (Tanjong Malim, 2017)
Examining attention cues for learning 3D modelling software: an eye-tracking study on instructional screencast by Sharmila Devi Pachiyappan